AN ANALYSIS OF DECLARATIVES AND DIRECTIVES USED IN THE JAKARTA POST ENGLISH DAILY NEWSPAPER - Saputro, Suswanto Ismadi Megah; Andriati, Yuni; Sugiharti, Sri (English Department, University of Riau Kepulauan, Batam,Indonesia, 2024)
This paper aims to investigate the speech acts used in the daily newspaper published in Jakarta, namely The Jakarta Post. The objective of the study is to find out the most dominant frequency of speech acts and the function of the types of declarative and directive speech acts. Data from this research were obtained from the English daily newspaper The Jakarta Post English. The results were questions 20 times (16.12%), declaring 15 times (12.09%), urging 15 times (12.09%), hope 14 times (11, 29%) dedication 12 times (9 .67%), warnings 11 times (8.87%), directives 9 times (7.25%), instructions 8 times (6.45%), requests 7 times (5.64%) and orders 7 times (5 .64%). Therefore, what is most often used in reporting news is questions. Therefore, this newspaper is intended to ask readers to know and understand the latest situation. Therefore, the newspaper, based on the data obtained, found that questions in speech acts were questions that functioned as questions as directive speech acts 20 times (16.12%) and the fewest types of directives that functioned as expectations were used only once. This paper shows that the type of request resulting from declaratives for requests is 7 times (5.64%) and commands 7 times (5.64%). This study found that questions showed the highest result. It implies that questions used to direct people in order to soften the words or more polite.